Distinct and overlapping functions of YAP and TAZ in tooth development and periodontal homeostasis - Ma, Jing; Fan, Haixia; Geng, Haixia (Frontiers in Cell and Developmental Biology, 2024)
Orthodontic tooth movement (OTM) involves mechanical–biochemical signal transduction, which results in tissue remodeling of the tooth–periodontium complex and the movement of orthodontic teeth. The dynamic regulation of osteogenesis and osteoclastogenesis serves as the biological basis for remodeling of the periodontium, and more importantly, the prerequisite for establishing periodontal homeostasis. Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are key effectors of the Hippo signaling pathway, which actively respond to mechanical stimuli during tooth movement. Specifically, they participate in translating mechanical into biochemical signals, thereby regulating periodontal homeostasis, periodontal remodeling, and tooth development. YAP and TAZ have widely been considered as key factors to prevent dental dysplasia, accelerate orthodontic tooth movement, and shorten treatment time. In this review, we summarize the functions of YAP and TAZ in regulating tooth development and periodontal remodeling, with the aim to gain a better understanding of their mechanisms of action and provide insights into maintaining proper tooth development and establishing a healthy periodontal and alveolar bone environment. Our findings offer novel perspectives and directions for targeted clinical treatments. Moreover, considering the similarities and differences in the development, structure, and physiology between YAP and TAZ, these molecules may exhibit functional variations in specific regulatory processes. Hence, we pay special attention to their distinct roles in specific regulatory functions to gain a comprehensive and profound understanding of their contributions.